A new tungsten-free γ–γ' Co–Al–Mo–Nb-based superalloy. (15th March 2015) - Makineni, S.K.; Nithin, B.; Chattopadhyay, K.
Abstract : Graphical abstract: Abstract : We present the first report of a tungsten-free cobalt-based superalloy having a composition Co–10Al–5Mo–2Nb. The alloy is strengthened by cuboidal precipitates of metastable Co3 (Al, Mo, Nb) distributed throughout the microstructure. The precipitates are coherent with the face-centred cubic γ-Co matrix and possess ordered L12 structure. The microstructure is identical to the popular γ–γ' type nickel-based superalloys and that of recently reported Co–Al–W-based alloys. Being tungsten free, the reported alloy has higher specific proof stress compared to existing cobalt-based superalloys.